Food, philosophy, and intellectual property : fifty case studies - Bonadio, Enrico; Borghini, Andrea (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
"This is a book about food, philosophy, and intellectual property rights. Taken separately, these are three well-known subjects; but it is uncommon to consider them together. Delivering a rich field of disputes, the book is comprised of 50 case studies, organized around eight themes: images; genericity and descriptiveness; language traps; procedures; menus, recipes, and creativity; boundaries; biotech; and empowerment. The introductory chapter frames the selection of cases and encourages readers to look beyond them, envisaging new lenses to look at food vis-à-vis intellectual property. The terrain encompassed is wide-ranging and reaches out to fine-grained aspects of food products, recipes, and cooking. Conceived for a wide scope of readers, the volume ultimately interrogates the links between food and cultural identity, bringing to the fore the ethical, political, aesthetic worth of culinary arts and gastronomic experiences. This accessible book will be of value to scholars, students, practitioners and others with interests in the areas of intellectual property, food law and food studies"--
Images -- Genericity and descriptiveness -- Language traps -- Procedures -- Menus, recipes, and creativity -- Boundaries -- Biotechnology -- Empowerment.
Keywords: Food law and legislation; Food industry and trade -- Patents; Food -- Patents; Food -- Philosophy; Food -- Biotechnology; Intellectual property (Intellectual property); LAW / Intellectual Property / General